Jesus + nothing = everything - Tchividjian, Tullian (Wheaton, Ill. : Crossway, 2011)
It's so easy to forget what the Christian faith is all about. We struggle so much, work so hard, and fail so often that we frequently sense something in the equation of life must be missing. Tullian Tchividjian argues that what we are missing is the gospel -- a fuller, more powerful understanding of Jesus and what his finished work means for everyday life. During a year of great turmoil, Pastor Tchividjian discovered the power of the gospel in his own life. Sharing his story of how Jesus became more real to him, Tchividjian delves deeply into the fundamentals of the faith, explaining the implications of Christ's sufficiency -- a revelation that sets us free and keeps us anchored through life's storms. Ultimately, Tchividjian reminds us that Jesus is the whole of the equation as he boldly proclaims that Jesus plus nothing really is everything. - Publisher.
God's mercy in my misery -- Wanting it all -- Still searching -- Black holes -- Jesus, all and more -- News : the biggest and best -- Fully exposed -- Out of the shadows -- Everything now, and more coming -- Our full response -- In the now -- All glorious.
Includes bibliographical references (p. 211-213) and index.
Keywords: Christian life -- Presbyterian authors